Elcie, an elderly care companion robot - Chang, Crystal Xuan Li (2019)
Personal robots have been around for a while but have had problems taking off due to their hefty price tags. Affordability of processors like the Raspberry Pi and Arduino opened up the possibility of mass market personal companion robots for the elderly which may tackle these problems. However, what we need to consider when designing such a system would be to balance the robustness of the software solutions with the computational abilities of these processors. The proposed system is El-C (from Elderly Companion), stylised as Elcie, an elderly companion robot. Elcie is optimised for its hardware and multi-pronged with: • Elderly tracking based on Haar cascade and DLib-based facial recognition tracking, • Social hub feature allowing elderly to interact with IOT and internet chat messenger Telegram • through intuitive speech and Quick Response (QR) codes as the user interface (UI).